KOMUNIKASI INTERPERSONAL UNTUK ANAK-ANAK DI PANTI ASUHAN HATI SUCI - Paramita, Sinta; Michael; Teguh, Fiola; Susanto, Angeline; Vimala Yanthi, Valencia (Jurnal Serina Abdimas, 2023)
Community Service Activities are carried out with the Hati Suci Orphanage Partners. Hati Suci Orphanage wants them to get a social environment that is generally obtained by children their age. In an effort to realize it, the Hati Suci Orphanage is faced with various challenges, one of which is the approach with children and the approach between one child and another, or how they carry out interpersonal communication. Interpersonal communication is an interaction process carried out between two or more people to convey messages that involve individuals as senders of messages and other individuals as recipients of messages that are useful for establishing positive social relationships. Therefore, we provide a solution by providing an understanding of how to carry out good interpersonal communication with others and people who are younger or older with the aim of training the self-confidence of the orphans. We do this understanding through the presentation of the material we have prepared in front of the orphans. The output we will produce is in the form of research articles published on kompas.com. The method of implementing this PKM activity has an implementation stage, that is, we conduct an informal presentation of interpersonal communication material to the children at the Hati Suci Orphanage. Participation of partners, namely providing space at the orphanage for presentation of material and scheduling meetings with orphanage children for presentation of the material. Description of the duties of team members, we have our respective roles in order to support PKM activities so that they run well. For additional outdoor plans, we will create a placard and flyer design regarding our material. In order to realize this PKM activity, we prepared this proposal with the title "The Role of Interpersonal Communication in Practicing Self-Confidence at the Hati Suci Orphanage". Kegiatan Pengabdian kepada Masyarakat dilakukan dengan Mitra Panti Asuhan Hati Suci. Panti Asuhan Hati Suci ingin mereka mendapatkan lingkungan sosial yang pada umumnya didapatkan oleh anak seusia mereka. Dalam upaya merealisasikannya, Panti Asuhan Hati Suci dihadapkan dengan berbagai tantangan salah satunya adalah pendekatan dengan anak-anak dan pendekatan antara satu anak dengan yang lain, atau bagaimana mereka melakukan komunikasi Interpersonal. Komunikasi interpersonal adalah proses interaksi yang dilakukan antara dua orang atau lebih untuk menyampaikan pesan yang melibatkan individu sebagai pengirim pesan dan individu lain sebagai penerima pesan yang berguna untuk menjalin hubungan sosial yang positif. Oleh karena itu, kami memberikan solusi dengan memberikan pemahaman mengenai bagaimana cara melakukan komunikasi interpersonal yang baik terhadap sesama maupun orang yang lebih muda atau tua dengan tujuan melatih kepercayaan diri anak-anak panti. Pemahaman ini kami lakukan melalui pemaparan materi yang telah kami siapkan di depan anak-anak panti. Luaran yang kami akan hasilkan berupa artikel hasil penelitian yang diterbitkan di kompas.com. Metode pelaksanaan kegiatan PKM ini ada tahap pelaksanaan yaitu, kami melakukan sebuah pemaparan materi tentang komunikasi Interpersonal secara informal kepada anak-anak di Panti Asuhan Hati Suci. Partisipasi mitra yaitu menyediakan ruangan di panti asuhan untuk pemaparan materi serta menjadwalkan pertemuan dengan anak-anak panti untuk pemaparan materi tersebut. Uraian tugas anggota tim, kami mempunyai peran masing-masing dalam rangka mendukung kegiatan PKM agar berjalan dengan baik. Untuk rencana luaran tambahan, kami akan membuat desain plakat dan selebaran mengenai materi kami. Dalam rangka mewujudkan kegiatan PKM ini kami menyusun proposal ini dengan judul “Peran Komunikasi Interpersonal Dalam Melatih Kepercayaan Diri di Panti Asuhan Hati Suci”.